PCSK9 deficiency reduces insulin secretion and promotes glucose intolerance: the role of the low-density lipoprotein receptor. (2nd July 2018) - Da Dalt, Lorenzo; Ruscica, Massimiliano; Bonacina, Fabrizia; Balzarotti, Gloria; Dhyani, Ashish; Di Cairano, Eliana; Baragetti, Andrea; Arnaboldi, Lorenzo; De Metrio, Simona; Pellegatta, Fabio; Grigore, Liliana; Botta, Margherita; et al.
Abstract: Aims: PCSK9 loss of function genetic variants are associated with lower low-density lipoprotein cholesterol but also with higher plasma glucose levels and increased risk of Type 2 diabetes mellitus. Here, we investigated the molecular mechanisms underlying this association. Methods and results: Pcsk9 KO, WT, Pcsk9/Ldlr double KO (DKO), Ldlr KO, albumin AlbCre+/Pcsk9 LoxP/LoxP (liver-selective Pcsk9 knock-out mice), and AlbCre-/Pcsk9 LoxP/LoxP mice were used. GTT, ITT, insulin and C-peptide plasma levels, pancreas morphology, and cholesterol accumulation in pancreatic islets were studied in the different animal models. Glucose clearance was significantly impaired in Pcsk9 KO mice fed with a standard or a high-fat diet for 20 weeks compared with WT animals; insulin sensitivity, however, was not affected. A detailed analysis of pancreas morphology of Pcsk9 KO mice vs. controls revealed larger islets with increased accumulation of cholesteryl esters, paralleled by increased insulin intracellular levels and decreased plasma insulin, and C-peptide levels. This phenotype was completely reverted in Pcsk9/Ldlr DKO mice implying the low-density lipoprotein receptor (LDLR) as the proprotein convertase subtilisin/kexin Type 9 (PCSK9) target responsible for the phenotype observed. Further studies in albumin AlbCre+/Pcsk9 LoxP/LoxP mice, which lack detectable circulating PCSK9, also showed a complete recovery of the phenotype, thus indicating that circulating, liver-derived PCSK9, the principal target of monoclonal antibodies, does not impact beta-cell function and insulin secretion. Conclusion: PCSK9 critically controls LDLR expression in pancreas perhaps contributing to the maintenance of a proper physiological balance to limit cholesterol overload in beta cells. This effect is independent of circulating PCSK9 and is probably related to locally produced PCSK9.